Functional regulation of monocyte-derived dendritic cells by microRNAs - Zhan, Yifan (Protein Cell, 2012)
Dendritic cells (DCs) as a rare type of leukocytes play an important role in bridging the innate and adaptive immune system. A subset of DCs, monocyte-derived dendritic cells (moDCs), exists in very low numbers at steady state but become abundant in inflammatory states. These inflammation-associated DCs are potent producers of pro-inflammatory cytokines and potent inducers of T helper differentiation. They behave as a “double-edge” sword so that they not only mediate protective immunity but also immuno-pathology. It is still incompletely understood how their function is regulated. Emerging evidence indicates that microRNAs (miRNAs), as a new class of gene regulators, potently regulate the function of moDCs. Here we summarize recent progress in this area.